PEMANTAUAN EFEKTIVITAS OBAT ANTI TUBERKULOSIS BERDASARAKAN PEMERIKSAAN SPUTUM PADA PENDERITA TUBERKULOSIS PARU - Siti Thomas Zulaikhah; Turijan - (JURNAL KESEHATAN, 2010)
Pulmonary tuberculosis (TB) in Indonesia is still a major problern and is the third cause of death in the world after Chinq and India. The principle of treatment is given in 2 phases, namely an intensive and advanced stage. Conversion target of at least 80 % in the intensive phase. Monitoring of treatment outcomes in adults conducted by the microscopic re-examination of sputum at the end of the 2nd month intensive phaseof treatment. Sputum examination at the end of intensive phase conducted to determine whether there has been conversion of sputum, which changes from positive to negative smear. Thirty sputum samples ofpatients with pulmonary TB (tuberculosis) which have made preparations to meet the inclusion criteria, carried out with qcid-fost staining Ziehl Neelsen method qnd examined microscopically by counting thenumber of smear positive per 100 field of view. OAT patients were given intensive phase for 2 montla and then a week before the end of the month of the 2nd re-examination of sputum performed microscopically. The results obtqined by dffirent test was then performed with llilcoxon test.The average of smear positive before treatment was 222/100 56/100 LP where the minimum amount and maximum 1139/ I00LP LP. The averqge of smear positive after treatment was I6/100 LP where the minimumamount 0 / 100 LP and muimum 104/100LP. As many as 73.i94 had positive sputum smear conversion after intensive phase of treatment. After the Wilcoxon test to the number of smear positive before and aftertreqtment got p-value : 0.0001 (p-value <0.05). There was significant dffirence between the number of smear positive before and after treatment in patients with pulmonary tuberculosri, so it can be concludedthat the Anti-Tuberculosis Drug effectively provided to the new pulmonary tuberculosis patients. Anti- Tuberculosis Drugs should be swallowed on a regular basis according to the instructions and do not stop taking the medication before the treatment is completed in order to avoid drug resistance, although at the end of intensive phase of treatment is obtained the number of smeor negative, but must continue treatment atan advanced stage to avoid recurrence.Keywords : Anti-Tuberculosis Drugs, Sputum pulmonary tuberculosis patients